DEVELOPMENT OF GOOGLE SITES WEB-BASED INTERACTIVE LEARNING MEDIA ON TEMPERATURE, HEAT, AND EXPANSION MATERIALS FOR JUNIOR HIGH SCHOOL STUDENTS - Salsabila, Diva; Diliarosta, Skunda (Department of Science Education, 2024)
The development of information and communication technology caused a change to digital-based learning methods aimed to simplify the delivery of learning materials for 7th-grade students. Observation held in several schools in Padang shows that learning media in the form of printed books no longer attracts students' attention. This research purposed to create a valid and practical interactive learning media based on the Google Sites website about temperature, heat, and expansion. The type of this research is Research and Development (R&D) using the ADDIE model, which is done only until the development stage. The validity test result shows an average kappa moment value of 0.94 within a very high validity category. The practicality test among teachers shows an average kappa moment (k) value of 0.95 within a very high validity category, and the practicality test among students shows an average kappa (k) moment value of 0.78 within a high validity category. Based on these results, we can conclude that Google Site web-based interactive learning media on temperature, heat, and expansion material is valid and practical.